(untitled) (Acta Polytechnica CTU Proceedings, 2024)
The paper deals with the examination of the ageing effects on the mechanical properties stability of 3D printed material via stereolithography under compression when subjected to various conditions, including UV radiation, X-rays, and the effects of time, from the opening of the bottle with the material to the 3D-printing process. The sets of samples under investigation were subjected to quasi-static and dynamic compression loading using an Split Hopkinson Pressure Bar. The aim of this paper is to investigate the long-term stability of the samples in terms of their mechanical properties and material behaviour and their degradation pattern. Despite the manufacturer’s information, it was found that the mechanical behaviour of the printed samples was significantly affected by the ageing process.